2013
DOI: 10.1002/cbin.10150
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of adipogenic differentiation by muscle cell‐induced decrease in genes related to lipogenesis in muscle and fat co‐culture system

Abstract: Intercellular signalling communication between adipose and muscle tissue has been investigated. To test the effect of muscle cells on adipogenic gene expression, we utilised an in vitro co-culture system, in which fat (3T3-L1) and muscle (L-6) cells were physically separated but chemically exposed each other via insert with 0.4 µm porous membrane. When 3T3-L1 and L-6 cells reached at 80 and 40% confluence, respectively in separate wells, L-6 cells grown in insert were transferred onto 6-well plates where 3T3-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Most studies of the regulation of adipogenesis have been conducted in cultured primary preadipocyte cultures or 3T3-L1 secondary preadipocyte cultures. A few studies have investigated the differentiation of bovine adipocytes and myoblasts in single cultures ( Chung et al, 2006a ; Ouellette et al, 2009 ), and we are aware of three studies describing the interaction between adipocytes and myoblastic cells in a co-culture system ( Hausman et al, 2005 ; Choi et al, 2013a ; Park et al, 2013 ), two of which originated from our laboratory ( Choi et al, 2013a ; Park et al, 2013 ). We have used this set of genetic markers of adipose tissue differentiation ( C/EBPβ , PPARγ ) and lipid metabolism ( AMPKα , CPT1β , GPR43 , SCD ) in studies of the effects of fatty acids on bovine preadipocytes ( Chung et al, 2006a ) and mature adipose tissues ( Smith et al, 2012 ; Choi et al, 2013a ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of the regulation of adipogenesis have been conducted in cultured primary preadipocyte cultures or 3T3-L1 secondary preadipocyte cultures. A few studies have investigated the differentiation of bovine adipocytes and myoblasts in single cultures ( Chung et al, 2006a ; Ouellette et al, 2009 ), and we are aware of three studies describing the interaction between adipocytes and myoblastic cells in a co-culture system ( Hausman et al, 2005 ; Choi et al, 2013a ; Park et al, 2013 ), two of which originated from our laboratory ( Choi et al, 2013a ; Park et al, 2013 ). We have used this set of genetic markers of adipose tissue differentiation ( C/EBPβ , PPARγ ) and lipid metabolism ( AMPKα , CPT1β , GPR43 , SCD ) in studies of the effects of fatty acids on bovine preadipocytes ( Chung et al, 2006a ) and mature adipose tissues ( Smith et al, 2012 ; Choi et al, 2013a ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from co-culture systems have shown that adipocytes induce insulin resistance (Dietze et al, 2002), and inhibit differentiation (Takegahara, Yamanouchi, Nakamura, Nakano, & Nishihara, 2014) and atrophy (Pellegrinelli et al, 2015) of muscle cells. Furthermore, adipogenesis of mesenchymal adipocyte progenitors or 3T3-L1 cells is inhibited by the presence of muscle satellite cells or L6 muscle cells (Park, Baek, & Choi, 2013;Uezumi et al, 2010). However, it is still unclear how myogenic and adipogenic cells communicate with each other in the extracellular niche within skeletal muscle.…”
mentioning
confidence: 99%
“…In a mouse model for DMD ( mdx mouse), they seem to provide the main source of increased fibrogenic or adipose tissue in pathological muscle [ 123 ]. Interestingly, a co-culture of fat (3T3-L1) and muscle (L-6) in physical separation but with chemically reciprocal exposure resulted in suppressed lipogenic gene expression and reduced GPDH-activity, suggesting an inhibitory influence of skeletal muscle on adipogenic differentiation [ 124 ]. A co-culture of human fat and skeletal muscle cells, obtained from different muscle cell and fat cell donors, showed induction of insulin resistance in human muscle cells through the release of fat cell factors [ 125 , 126 ], underlining the alternating influence of muscle on fat and vice versa.…”
Section: From 2d Cell Culture To Human Organs-on-a-chipmentioning
confidence: 99%